Study of the Oxidative and Microbiological Stability of Nitrite-Reduced, Vacuum-Packed, Refrigerated Lamb Sausages Supplemented with Red Propolis Extract - Luciana Ruggeri Menezes Gotardo; Francisco Allan Leandro de Carvalho; Dannaya Julliethy Gomes Quirino; Carmen Sílvia Favaro-Trindade; Severino Mathias de Alencar; Alessandra Lopes de Oliveira; Marco Antonio Trindade (Foods, 2023)
Vacuum-packed lamb sausages with or without red propolis extract and a reduced sodium nitrite content were evaluated for oxidative and microbiological stability during storage for 21 days at 2 °C. The following treatments were evaluated: EN150 (control, base formulation (BF) + 500 mg/kg sodium erythorbate and 150 mg/kg sodium nitrite); EN75 (BF + 500 mg/kg sodium erythorbate and 75 mg/kg sodium nitrite); P1N75 (without the addition of erythorbate, BF + 1800 mg/kg propolis extract and 75 mg/kg sodium nitrite); and P2N75 (without the addition of erythorbate, BF + 3600 mg/kg propolis extract and 75 mg/kg sodium nitrite). Analyses were conducted to characterize the samples on day 0 with respect to the proximate composition (moisture, protein, fat, and ash) and sensory acceptance. Stability during refrigerated storage was evaluated on days 0, 7, 14 and 21 for the parameters pH, color profile (L*, a*, and b*), TBARs index (oxidative stability) and microbiological count of aerobic psychrotrophic microorganisms. Texture profile, cooking weight loss (WLC), peroxide index and free fatty acids were evaluated on days 0 and 21. The treatments with propolis and reduced nitrite (EN150 and P1N75) showed a red color intensity (a*) similar to the treatment with erythorbate and the same nitrite content (EN75) at the end of storage, maintaining the characteristic reddish color of the sausages. The extract slowed down lipid oxidation during storage, especially P2N75, which showed the lowest level of TBARS (0.39 mg MDA/kg) and the peroxide index (2.13 mEq g O2) on day 21. The residual nitrite value in EN75 was the lowest (p < 0.05) on day 21, showing that synthetic antioxidants are more efficient than the extract in nitrite reduction reactions. The results for the counts of psychrotrophic microorganisms showed that the extract did not have the expected antimicrobial effect on the growth of this microorganisms, and leveling the results revealed no differences (p < 0.05) between the treatments. Despite the red propolis extract not showing a significant antimicrobial improvement in lamb sausages, it can be considered a healthy option with good prospects for replacing synthetic antioxidants with a natural product.